(untitled) - Layman, C. Stephen (Boston, 2005)
This introductory level text carries the conviction that logic is the most important course that college students take. The Power of Logic provides balanced coverage of informal logic, traditional categorical logic, and modern symbolic logic, while its companion online supplement, Logic Tutor, offers a wealth of applications for the concepts discussed. Layman’s direct and accessible writing style, along with his plentiful examples and imaginative exercises, make this the best text for today's logic classes
Keywords: Logic,Logic học